Effects of the application protocol and bonding strategy of the universal adhesive on dentin previously impregnated with bioceramic sealer - Oliveira Barros, Antonia Patricia [UNESP]; Lucas de Sousa Gomes Costa, Joatan; Camilo do Carmo Monteiro, Jardel [UNESP]; Galvani, Lucas David [UNESP]; Ferrarezi de Andrade, Marcelo [UNESP]; Cury Saad, José Roberto [UNESP]; Kuga, Milton Carlos [UNESP] (Elsevier, 2024)
Purpose: To evaluate the effects of the application of universal adhesive with manual brush (MB) or rotary brush (RB), in the etch-and-rinse (ER) or self-etching (SE) strategy, on the bond strength, adhesive layer thickness, and adhesive failure pattern to dentin impregnated with bioceramic sealer, at 24 h and 1 year. Materials and methods: Eighty-eight bovine incisor crowns were impregnated with bioceramic sealer was kept for 15 min and cleaned with cotton soaked in distilled water. They were then divided into four groups (n = 22): ER-MB, ER-RB, SE-MB, SE-RB. Subsequently, the specimens were restored with Filtek Z-250 resin. The adhesive layer thickness was individually analyzed using laser confocal microscope. Bond strength was assessed through microtensile testing, and the failure pattern was examined using a stereomicroscope. Data were analyzed by one-way ANOVA/Tukey's tests (α = 0.05). Results: The adhesive layer thickness provided by ER-MB and SE-MB was greater than that provided by ER-RB and SE-RB (P < 0.05). ER-MB showed the lowest bond strength at 24 h (P < 0.05). At 1 year, SE-MB and SE-RB exhibited the highest bond strength values (P < 0.05). ER-MB demonstrated a higher incidence of adhesive failure at 24 h. At 1 year, SE-RB and SE-MB showed a higher incidence of mixed failure. Conclusion: The use of Scotchbond Universal® adhesive in the etch-and-rinse strategy applied with a MB negatively affects bond strength at 24 h, worsening after 1 year of control, regardless of the application protocol.
Keywords: Bioceramic Sealer; Bond strength; Failure modes; Protocols; Root canal filling material